Perspectivas análiticas para el estudio de la relación inmigración: parentesco en el contexto cubano - Espronceda Amor, María Eugenia (2011)
O texto aborda o processo de formação dos grupos de descendência em Cuba, a partir das migrações de origem francófona (preferencialmente haitiana) e anglófona (jamaicana). O parentesco como suporte da transmissão da cultura constitui a tese central desenvolvida. Este é, parcialmente, responsável pela conservação enriquecida das características culturais provenientes dos antepassados, em franca competição com outras instituições, organizações e grupos sociais. O conteúdo do texto alarga as investigações realizadas acerca da chamada imigração antilhana, propondo novas leituras sobre a relação cultura-parentesco. The text approaches the process of formation of the descendant groups in Cuba, starting from the immigrations of Caribbean French speakers, preferably Haitian and English speakers (Jamaicans). Kinship and marriage as a support to the transmission of culture constitutes the central thesis developed. They are responsible, partially, for the enriched conservation of the cultural features coming from their ancestors in competition with other institutions, organizations and social groups. The content of this article widens other researches carried out about the so called “imigración antillana”, proposing new viewpoints about the relationship between culture-kinship and marriage.